Antisocial Behavior and Victimization Over 2-Year Follow-Up in Subgroups of Childhood Arrestees. Issue 18 (September 2019) - van Domburgh, Lieke; Geluk, Charlotte; Jansen, Lucres; Vermeiren, Robert; Doreleijers, Theo
Not only are childhood onset offenders at high risk of becoming serious persistent offenders, they are also at high risk of becoming victimized themselves. Furthermore, studies in the general population suggest that a combined perpetrator–victim group can be distinguished from a perpetrator-only and a victim-only group on individual and family risk factors. The current study investigated the co-occurrence of offending and victimization among first-time arrestees and the 2-year predictive value of previously found clusters of dynamic risk factors of offending. Childhood first-time arrestees ( N = 308; M age = 10.3, SD = 1.45) were clustered into three groups based on dynamic risk factors of offending in the individual, peer, school, and family domains: a pervasive high, an externalizing intermediate, and a low problem group. Police records and self-report data on re-offending and victimization of these children were collected over a 2-year follow-up period. Compared with the low problem group, the prevalence of re-offending was higher in both the externalizing intermediate group and the pervasive high group. The pervasive high group was most likely to display co-occurring future antisocial behavior and victimization. These findings emphasize that attention should be paid to victimization in addition to future antisocial behavior, especially if additional internalizing and family problems are present. Furthermore, the differences in re-offending and victimization between subgroups of childhood onset offenders stress the need for specific interventions tailored to the risk profile of a child.